2021
DOI: 10.3390/polym13234126
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of Polymer Gears Fabricated by Differential Pressure Vacuum Casting and Fused Deposition Modeling

Abstract: In recent years, polymer gears have gradually become more widely employed in medium or heavy-duty conditions based on weight reduction in transmission systems because of low costs and low noise compared to metal gears. In the current industry, proposing a cost-effective approach to the manufacture of polymer gears is an important research issue. This paper investigates the wear performance of polymer gears fabricated with eight different kinds of materials using differential pressure vacuum casting and additiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It was found that this hybrid has a regular layered morphology, which increased the mechanical strength of the product. The tensile strength increased by 44% [93,94]. The vacuum casting method in silicone molds uses less expensive tools and materials, and is therefore a good alternative to existing microform production methods.…”
Section: Vacuum Casting (Vc) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that this hybrid has a regular layered morphology, which increased the mechanical strength of the product. The tensile strength increased by 44% [93,94]. The vacuum casting method in silicone molds uses less expensive tools and materials, and is therefore a good alternative to existing microform production methods.…”
Section: Vacuum Casting (Vc) Methodsmentioning
confidence: 99%
“…It was found that this hybrid has a regular layered morphology, which increased the mechanical strength of the product. The tensile strength increased by 44% [ 93 , 94 ].…”
Section: A Review Of the Literaturementioning
confidence: 99%
“…One of the factors that determines the quality of injection molded parts is the weld line [ 50 , 75 , 76 ]. The weld line refers to the process in which the liquid material is divided into two or more flows in the cavity during the injection process and merged together after a period of time [ 51 , 77 , 78 , 79 ].…”
Section: Injection Molding Processmentioning
confidence: 99%
“…Polymer gears have a number of drawbacks, the most notable of which are reduced load-bearing capacity, poorer thermal conductivity, lower temperature stability, and poor manufacturing precision. While the load-bearing capacity is extremely important, several studies can be found on improving this property, either with improved gear design [2,3] or improved materials [4][5][6]. However, there is a lack of systematic studies addressing the geometrical quality of injection moulded polymer gears, since only a few studies can be found on this topic.…”
Section: Introductionmentioning
confidence: 99%